Postdoctoral scholars' perceptions of a university teaching certificate program. (6th July 2020) - Nowell, Lorelli; Laventure, Audrey; Räisänen, Anu; Strzalkowski, Nicholas; Kenny, Natasha
Abstract : Purpose: This study aims to explore postdoctoral scholars' experiences and perceptions of a teaching certificate program and identify how they use the knowledge and skills developed through the certificate program to improve their teaching practices. Design/methodology/approach: In this case study, the authors explored postdoctoral scholars' experiences and perceptions of a teaching certificate using a multiple methods and data sources including documents, course evaluations, interviews and surveys. Findings: The teaching certificate program helped postdocs learn the language and theory of teaching and learning in post-secondary education; practice specific strategies and develop confidence in how to teach; network with colleagues about teaching and learning; develop a reflective teaching practice; and contribute to the scholarship of teaching and learning. Practical implications: The findings from this study will inform efforts to develop new or refine existing approaches to promote teaching and learning professional development opportunities for postdoctoral scholars. Originality/value: This paper fulfills an identified need to study teaching and learning development for postdoctoral scholars.